Deep Learning Based Adaptive Strategy Assistance in Supporting Learning Quality at Muhammadiyah University of Palembang - Houtman; Agung Nugroho; Inda Puspita Sari (KENDURI : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
The development of educational technology requires universities to adopt an adaptive and student-centered learning approach. However, the implementation of a deep learning approach in the learning process still faces various obstacles, such as limited lecturer understanding, a lack of implementation strategies, and suboptimal technology integration in teaching and learning activities. This community service activity aims to improve lecturers' competency in designing and implementing deep learning-based adaptive strategies to support the quality of learning at Muhammadiyah University of Palembang. The methods used include socialization, training, intensive mentoring, and evaluation. The training focused on understanding the concept of deep learning, designing adaptive learning, and utilizing supporting technology. Next, mentoring was provided in the development of learning tools and their implementation in the classroom. Evaluation was carried out through observation, questionnaires, and analysis of learning quality improvements. The results of the activity showed an increase in lecturers' understanding and skills in developing deep learning-based learning strategies. In addition, there was an increase in active student participation, critical thinking skills, and the quality of learning interactions. Lecturers were also able to integrate technology more effectively into the learning process. The conclusion of this activity is that mentoring with deep learning-based adaptive strategies is effective in improving the quality of learning in higher education. This program is recommended to be implemented sustainably with the support of institutional policies to achieve more optimal improvements in the quality of education.